Piezoelectric Photoacoustic System for Fluid Flow Monitoring - Chua, Hui Ling; Huong, Audrey (International Journal of Integrated Engineering, 2020)
The aim of this study is to investigate the feasibility of using a laboratory assembled piezoelectric based photoacoustic (PA) system for noncontact monitoring fluid flow. This is to overcome the drawbacks of some existing fluid flow detection systems, which include expensive equipment and their maintenance cost, limited sensitivity and specificity in detecting signals from restricted regions or at low flow velocity. The produced PA signal waves detected by a piezoelectric transducer used in this study was processed to determine the required phase value (Ф), which value was found to correlate linearly with fluid flow status. The fluid pressure difference of 1.16 pascals (Pa) and 11.90 Pa applied to the developed mock circulatory system was observed to produce changes in phase value with mean ± standard deviation (SD) ΔФ of 0.79 ± 0.07 rad and 2.17 ± 0.07 rad, respectively, suggesting a linear response of the developed system with changes in circulation system. This trend was supported with the relatively low absolute difference of 0.07 ± 0.01 rad in the predicted values as compared to that of the ground truth. This work concluded that the capabilities and simplicity of the proposed PA system renders it feasible for cost effective, non-destructive assessment of fluid flow in future studies.